PENGARUH STRUKTUR MODAL DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN TEKSTIL DAN GARMEN YANG TERDAFTAR DI BEI PERIODE 2019-2021 DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL INTERVENING - Hasanah, Kamilatul; Hamdun, Edy Kusnadi; Wiryaningtyas, Dwi Perwitasari (Fakultas Ekonomi dan Bisnis, 2023)
The purpose of this study is to find out the effect of capital structure and financial performance on firm value in textile and garment companies listed on Indonesia Stock Exchange (IDX)for 2019-2021 period with financial distress as an intervening variable. The population in this study is all textile and garment companieslisted on Indonesia Stock Exchange (IDX), involving 22 companies in 2019-2021 period. The sampling technique in this study uses purposive sampling by selecting 10 samples of data analysis. Data analysis and hypothesis testing in this study use Smart PLS 3.0 application.The results of this study show that capital structure has no significant effect on financial distress, while financial performance has a significant negative effect on financial distress. Capital structure, financial performance and financial distress do not have a significant effect on firm value. Capital structure and financial performance do not have a significant effect on firm value through financial distress.